Efficacy and safety of transcatheter aortic valve replacement in intermediate surgical risk patients: A systematic review and meta‐analysis. Issue 6 (4th March 2016) - Khan, Abdur Rahman; Khan, Sobia; Riaz, Haris; Luni, Faraz Khan; Simo, Herman; Bin Abdulhak, Aref; Bavishi, Chirag; Flaherty, Michael
Abstract : Background: The efficacy of transcatheter aortic valve replacement (TAVR) in aortic stenosis patients at high surgical risk has been established. The data on patients with intermediate risk is not conclusive. We performed a meta‐analysis of studies which compared TAVR with surgical aortic valve replacement (SAVR) in patients at intermediate surgical risk. Methods: Several databases searched from inception to February 2015 yielded 7 eligible studies with 2, 173 participants. The measured outcome of efficacy was all‐cause mortality. Data on safety included stroke, permanent pacemaker implantation (PPI), aortic regurgitation (AR), vascular access complications, and major bleeding. Outcomes were pooled and relative risk (RR) was calculated with the Mantel–Haenszel method. Results: There was no difference in either short‐term (RR, 1.02; 95% CI: 0.63–1.63; P  = 0.94; I 2  = 0%) or medium to long‐term all‐cause mortality (RR, 0.99; 95% CI: 0.81–1.21; P  = 0.91; I 2  = 0%). There was increased incidence of stroke (RR, 2.96; 95% CI: 0.87–10.09; P  = 0.08; I 2  = 0%), AR (RR, 3.59; 95% CI: 2.13–7.19; P  < 0.00001; I 2  = 2%), PPI (RR, 6.53; 95% CI: 1.91–22.32; P  < 0.003; I 2  = 0%) and vascular access complications (RR, 3.84; 95% CI: 0.65–22.76; P  < 0.14; I 2  = 48%) in patients with TAVR. There was a small, albeit increased risk of major or life threatening bleeding with SAVR as compared to TAVR (RR, 1.36; 95% CI: 1.04–1.80; P  < 0.03; I 2  = 0%). Conclusions: In this meta‐analysis we found that TAVR may be an acceptable alternative to SAVR in patients with intermediate risk for surgery. However, we must await evidence from the current large randomized trials before widespread adoption of this procedure is undertaken. © 2016 Wiley Periodicals, Inc.